Physical characterization and fluidization design parameters of wheat germ - Gili, Renato Daniel (2017)
Wheat germ is the embryo of de wheat seed, it contains a high tocopherol and protein content, and high quality proteins and fatty acids. Also, wheat germ has a considerable enzymatic activity that limits its shelf life. The aims of the study were to physically and sorptionally characterize wheat germ particles, select the more convenient model to describe the relationship between moisture content and water activity of wheat germ and to determine their design parameters of thermal fluidization process with air. The principal axes of the particle were measured by image analysis, and their dimensions and geometric parameters were calculated. Four isotherm models were fitted to experimental data. GAB model was the more accurate to explain the experimental data. The fixed bed density and the void fraction were measured. The fluid-dynamic studies permitted to determine laminar (277.46 ± 17.48) and turbulent (7.79 ± 0.69) coefficients of the Ergun equation and the minimum fluidization velocity (0.35 ± 0.02 m/s).